The perspective of climate-smart agricultural practices in the rice-wheat cropping system in Haryana, India - Rajesh Kumar,; Mehtab Singh, (National Geographical Journal of India, 2022)
Agricultural transformation is a process of change in agricultural practices and production. After the green revolution, a significant agricultural transformation has been recorded in Haryana. The cropping pattern of the state has shifted from multi-cropping to mono-cropping. The share of rice and wheat is about 87 percent of the total area under food grains. The present study emphasizes assessing the transforming agricultural practices in Haryana besides exploring the measures of sustainable climate-smart agricultural practices. The study is based on both primary and secondary data sources. Climatic data has been collected from Regional Meteorological Centre, Chandigarh and statistical abstracts of Haryana have been used for data related to major crops. To assess the adoption of climate-smart agricultural practices in Haryana, a primary survey was conducted in two different agro-climatic regions of the state. A cluster of five villages from each region has been selected. From each selected village, about 30 agricultural households have been surveyed. The vulnerability spider diagram and the fuzzy cognitive map are used to represent the level of adoption and perception of farmers regarding climate-smart agricultural practices. The result shows that excessive use of agro-chemicals in the rice-wheat cropping system has increased production, however, caused alterations in the chemical and physical properties of the soil and depletion of groundwater resources in the state. Changing climatic conditions has further aggravated these challenges.